Canadianization, Colonialism, and Decolonization: Investigating the Legacy of “Seventies Nationalism” in the Robin Mathews Fonds - Dean, Misao (Studies in Canadian Literature / Études en littérature canadienne, 2016)
The opening of the Robin Mathews Fonds at Library and Archives Canada in 2014 provides an opportunity to revisit Mathews’s role in the struggle to make Canadian literature a legitimate area of study in English departments. Mathews was instrumental in the founding of the Association for Canadian and Quebec Literatures; he advocated for more courses and graduate programs, as well as expanded scholarship in the field -- goals which he argued could not be reached unless more Canadians were hired in university English departments. Inspired by the anti-colonial nationalisms of the sixties and seventies, Mathews saw Canadian nationalism as anti-imperialist and anti-capitalist, and he argued that Canadian literature, rightly read, offered the materials for a collectivist counter-narrative to neoliberal capitalism. His work argued for the centrality of authors like Irene Baird, Earle Birney, Milton Acorn, and Dorothy Livesay to what he called “the tradition” of Canadian writing. While he was often accused of anti-Americanism, a more salient critique of his ideas targets his failure to grow beyond an “old left” view of race as a way to divide the working class. Mathews’s struggle to “Canadianize” English departments was a failure; Canadian literature consistently makes up just 8-10% of the course offerings in Canadian English departments, and in Canada the “English degree” is still a degree in English literature, instead of a degree in literatures in English.